Chan‐Evans‐Lam C−N Coupling Promoted by a Dinuclear Positively Charged Cu(II) Complex. Catalytic Performance and Some Evidence for the Mechanism of CEL Reaction Obviating Cu(III)/Cu(I) Catalytic Cycle. Issue 11 (15th April 2020) - Akatyev, Nikolay; Il'in, Mikhail; Il'in(Jr.), Mikhail; Peregudova, Svetlana; Peregudov, Alexander; Buyanovskaya, Anastasiya; Kudryavtsev, Kirill; Dubovik, Alexander; Grinberg, Valerij; Orlov, Victor; Pavlov, Alexander; Novikov, Valentin; et al.
Abstract: In the present study, we report the synthesis of a series of copper(II) complexes with a wide range of ligands and their testing in the copper catalyzed Chan‐Evans‐Lam (CEL) coupling of aniline and phenylboronic acid. The efficiency of the coupling was directly connected with the ease of the reduction of Cu(II) to Cu(I) of the complexes. The most efficient catalyst was derived from 4‐ t ‐butyl‐2, 5‐bis[(quinolinylimino)methyl]phenolate and two Cu(II) ions. Depending on the counter‐anion nature and the concentration of the reaction mixture, the reaction can be directed to predominant C−N‐bond formation. Forty‐three derivatives of diphenylamine were prepared under the optimized conditions. The proposed mechanism of the catalysis was based on the reduction potential of a series of complexes, molecular weight measurements of the catalytic complex in MeOH and the kinetic studies of aniline and phenylboronic acid coupling. In addition, an 1 H NMR experiment in a sealed NMR tube, without external oxygen supply available, proved that no complete Cu(II) to Cu(I) conversion was observed under the condition, ruling out the usually accepted mechanism of the C−N coupling, which included the oxygenation of the intermediately formed Cu(I) complexes after the key step of C−N conversion had already been completed. Instead, a mechanism was proposed, involving an oxygen molecule coordinated to two copper ions in the key C−N bond formation without any detectable conversion of the Cu(II) complexes to Cu(I). Abstract : From Russia with copper : The dinuclear complex derived from 8‐aminoquinoline and 2, 6‐diformyl‐4‐ tert ‐butylphenol was an efficient catalyst of CEL‐coupling reaction of phenylboronic acids and anilines. The counter‐ion nature played an important role in determining the selectivity of the side reactions. Some evidence was presented in favor of oxygen molecule present in the stage of C−N‐bond formation.